Predicting smoking abstinence with biological and self-report measures of adherence to varenicline: Impact on pharmacogenetic trial outcomes. (1st September 2018) - Peng, Annie R.; Schnoll, Robert; Hawk, Larry W.; Cinciripini, Paul; George, Tony P.; Lerman, Caryn; Tyndale, Rachel F.
Highlights: Salivary varenicline levels predict early and long-term abstinence. Self-report pill counts do not consistently predict abstinence. Possible varenicline level cut-points for distinguishing abstinence were examined. Varenicline levels are better than pill counts for identifying abstinent participants. Impact of biomarker on outcome can be better understood when adherence is confirmed. Abstract: Introduction: Adherence to pharmacotherapies for tobacco dependence, such as varenicline, is necessary for effective treatment. The relationship between varenicline adherence, determined by commonly used indirect (i.e., self-reported pill counts) and infrequently used direct (i.e., varenicline levels) methods, and abstinence outcomes have not been previously examined, nor has their impact on the outcomes of a genetically randomized clinical trial been assessed. Methods: At Week 1 following target quit date, self-reported pill count and salivary varenicline levels were obtained from participants (N = 376) in a smoking cessation clinical trial (NCT01314001). Point-prevalence abstinence was biochemically-verified by salivary cotinine at Week 1 and by exhaled carbon monoxide at Week 1, end-of-treatment, 6 and 12 months following treatment. Blood nicotine metabolite ratio (NMR) was obtained at baseline. Results: Adherent individuals based on varenicline levels were significantly more likely to be abstinent than non-adherent individuals at Week 1 (odds ratios [ORs] 1.92–3.16, p's≤0.006), end-of-treatment (OR = 2.53, p = .004), and six months following treatment (OR = 2.30, p = .03). In contrast, pill counts did not consistently predict abstinence. Including direct measures of adherence enhanced the association between rate of nicotine metabolism (NMR) and end-of-treatment abstinence; normal metabolizers (NMR ≥ 0.31) were significantly more likely than slow metabolizers (NMR < 0.31) to be abstinent at end-of-treatment (OR = 2.00, p = .005). Conclusion: Adherence based on salivary varenicline, rather than on pill counts, is predictive of Week 1 abstinence, irrespective of the biomarker of abstinence assessed, and of long-term abstinence. Direct measures of adherence enhance the ability to assess the impact of a biomarker or genetic marker on abstinence outcomes.